FRI0160 THE CORRELATION BETWEEN PREGNANCY, DISEASE ACTIVITY AND ADVERSE PREGNANCY OUTCOMES IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Cetin, C.; Saraç-Sivrikoz, T.; Ateş-Tikiz, M.; Torun, E. S.; Zarali, S.; Yalçinkaya, Y.; Gul, A.; Inanc, M.; Ocal, M. L.; Kalelioğlu, İ. and Artim-Esen, B.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) can present with acute disease flares/exacerbations during pregnancy and postpartum period. 1 These flares can cause adverse pregnancy outcomes (APO). Objectives: In this study, our pregnant SLE cohort, which was under medical surveillance of both our Rheumatology and Gynecology and Obstetrics departments was analyzed. We intended to determine the effects of pregnancy on disease activity and the correlation between disease flares and adverse pregnancy outcomes. Methods: 168 pregnancy data involving 136 patients with SLE meeting the ACR criteria were examined. Cumulative clinical, laboratory and serological parameters were described and disease activity and flares were calculated using SLEDAI-2K disease activity index during preconceptional six month period, during all trimesters of pregnancy, and during postpartum six month period. Patients with low lupus disease activity scores (LLDAS) during each of these periods were identified. Fetal/neonatal death, premature birth due to preeclampsia, eclampsia or HELLP syndrome, neonates small for gestational age were determined as adverse pregnancy outcomes. Relationship of APO with disease activity was studied and patients with APO were compared to patients without APO. Results: Mean SLEDAI-2K scores was 1.3±2.2 (0-16) during preconceptional six month period, 1.3±2.6 (0-16) during conception period, 1.7±3.2 (0-22) during first trimester, 1.4±2.7 (0-16) during second trimester, 1.5±3.3 (0-20) during third trimester and 3.5±5.4 (0-26) during postpartum six month period. Mean postpartum six month period SLEDAI-2K score was higher compared to the mean pregnancy SLEDAI-2K score (p<0.05). LLDAS was sustained in 79% of all pregnancies. 19% of pregnancies resulted in flares. 42% of these flares were severe and 58% were mild or moderate. 49% of severe flares occurred during the postpartum six month period and this percentage was significantly higher compared to each trimester (p<0.05). Most of the flares during pregnancy and postpartum period had mucocutaneous (37%), renal(35%) and hematological(25%) involvement. APO was observed in 34% of pregnancies (n=57). APO (+) group was characterized by significantly longer disease duration and higher disease activity in all periods compared to APO (-) group (142±70 vs 170±88 months, p<0.05). In APO (-) group, the proportion of patients with severe disease activity during all pregnancy periods and postpartum period was significantly low (%18 vs 35, p<0.05), while the proportion of patients with sustained LLDAS was much higher (%88 vs 70). Conclusion: Postpartum six-month period appears to have the highest risk for disease flares during SLE pregnancies. Disease activity during pregnancy increases the risk of APO. Patients with sustained LLDAS have significantly lower APO rates. In order to achieve a positive pregnancy outcome and lower maternal morbidity, regular follow up of patients during pregnancy and postpartum period by Rheumatology and Gynecology and Obstetrics Departments is necessary. References: [1]Eudy AM, et al. Ann Rheum Dis 2018;0 :1–6. doi:10.1136/annrheumdis-2017-212535 Disclosure of Interests: None declared